2022
DOI: 10.17712/nsj.2022.4.20220025
|View full text |Cite
|
Sign up to set email alerts
|

Review of electroencephalography signals approaches for mental stress assessment

Abstract: The innovation of electroencephalography (EEG) more than a century ago supports the technique to assess brain structure and function in clinical health and research applications. The EEG signals were identified on their frequency ranges as delta (from 0.5 to 4 Hz), theta (from 4 to 7 Hz), alpha (from 8 to 12 Hz), beta (from 16 to 31 Hz), and gamma (from 36 to 90 Hz). Stress is a sense of emotional tension caused by several life events. For example, worrying about something, being under pressure, and facing sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Prior studies have indicated that the deceleration of environmental alpha waves is indicative of cerebral problems and mental stress. [ 30 ] The alpha rhythm is most effectively visualized when individuals engage in a state of rest with their eyes closed, and its amplitude is diminished on eye-opening and engagement in cognitive processes. Individuals diagnosed with stress disorder exhibit a lack of simple alpha activity.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have indicated that the deceleration of environmental alpha waves is indicative of cerebral problems and mental stress. [ 30 ] The alpha rhythm is most effectively visualized when individuals engage in a state of rest with their eyes closed, and its amplitude is diminished on eye-opening and engagement in cognitive processes. Individuals diagnosed with stress disorder exhibit a lack of simple alpha activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is not known how beta power relates to amyloid load in the context of DS. Taking benzodiazepines causes an increase in beta activity [39], and some DS patients have taken these drugs. Furthermore, beta activity is increased under stress [40], and people with DS often experience anxiety disorders [41].…”
Section: Discussionmentioning
confidence: 99%
“…To quantify cognitive stress, brainwaves are recorded using an electroencephalogram (EEG). EEG records electrical activity in the brain from which mental disposition can be deduced as brain wave states, of which there are five: delta (0.5Hz-4Hz), theta (4Hz-7Hz), alpha (8Hz-12Hz), beta (16Hz-31Hz), and gamma (36Hz-90Hz) [41]. High frequency brain waves are associated with greater cognitive arousal, while low frequency brain waves indicate a calmer mental state.…”
Section: Methodsmentioning
confidence: 99%